Territorial governance in Portugal: Institutional change or institutional resilience? - Oliveira, Carlos; Breda-Vázquez, Isabel (TH Zürich, NSL, 2011)
In den letzten Jahrzehnten sah sich Portugals territoriale Governance einem gehörigen Veränderungsdruck ausgesetzt. Dabei spielt die Mitgliedschaft in der Europäischen Union eine zentrale Rolle, sowohl unmittelbar durch die Einführung neuer Instrumente in räumlichen Entwicklungsprogrammen als auch mittelbar beeinflusst durch die Konfrontation mit neuen Planungskonzepten. Dennoch zeigen die nationalen Kontexte eine große Widerstandsfähigkeit gegen die Prozesse der Europäisierung. Diese beiden widerstrebenden Tendenzen werden im Beitrag anhand des Beispiels interkommunaler Zusammenarbeit demonstriert.

In the last few decades, Portuguese territorial governance has been subject to considerable pressure for change. European Union membership has played a central role in this process, either directly through the introduction of new instruments, such as development programs, or indirectly through influences on planning concepts. However, domestic contexts often develop a high degree of resilience in the presence of these Europeanization processes. This is the case in Portugal, where programming instruments and the formal planning system evolved differently, reflecting different ways of combining change and resilience. The article addresses this issue by comparing these two facets of Portuguese territorial governance in the case of inter-municipal coordination.
Keywords: Raumplanung; Planungssystem; Planungsorganisation; Raumplanungsbehörde; Raumplanungsinstitution; Planungskonzept; Kommunale Zusammenarbeit; Planungspraxis; Raumplanungspolitik; Europäisierung; Planungskultur; Raumplanungshoheit; Raumplanungsprogramm; Akteur; Akteursforschung; Kohäsion; Territoriale Agenda der EU; Raumentwicklungspolitik; Territoriale Governance; Governance; Planungsgeschichte